Cardiac and vascular health in late preterm infants. (19th February 2022) - Dissanayake, Hasthi U.; McMullan, Rowena L.; Kong, Yang; Caterson, Ian D.; Celermajer, David S.; Phang, Melinda; Raynes-Greenow, Camille; Polson, Jaimie W.; Gordon, Adrienne; Skilton, Michael R.
Abstract: Adults who were born preterm are at increased risk of hypertension and cardiovascular disease in later life. Infants born late preterm are the majority of preterm births; however, the effect of late preterm on risk of cardiovascular disease is unclear. The objective of this study was to assess whether vascular health and cardiac autonomic control differ in a group of late preterm newborn infants compared to a group of term-born infants. A total of 35 healthy late preterm newborn infants, with normal growth (34–36 completed weeks' gestation) and 139 term-born infants (37–42 weeks' gestation) were compared in this study. Aortic wall thickening, assessed as aortic intima–media thickness (IMT) by high-resolution ultrasound, and cardiac autonomic control, assessed by heart rate variability, were measured during the first week of life. Postnatal age of full-term and late preterm infants at the time of the study was 5 days (standard deviation [SD] 5) and 4 days (SD 3), respectively. Infants born late preterm show reduced aortic IMT (574 μm [SD 51] vs. 612 μm [SD 73]) and reduced heart rate variability [log total power 622.3 (606.5) ms 2 vs. 1180. 6 (1114.3) ms 2 ], compared to term infants. These associations remained even after adjustment for sex and birth weight. Infants born late preterm show selective differences in markers of cardiovascular risk, with potentially beneficial differences in aortic wall thickness in contrast to potentially detrimental differences in autonomic control, when compared with term-born control infants. These findings provide pathophysiologic evidence to support an increased risk of hypertension and sudden cardiac death in individuals born late preterm.